A review of synthetic fuels for passenger vehicles. (November 2019) - Hänggi, Severin; Elbert, Philipp; Bütler, Thomas; Cabalzar, Urs; Teske, Sinan; Bach, Christian; Onder, Christopher
Abstract: Synthetic fuels produced with renewable surplus electricity depict an interesting solution for the decarbonization of mobility and transportation applications which are not suited for electrification. With the objective to compare various synthetic fuels, an analysis of all the energy conversion steps is conducted from the electricity source, i.e., wind-, solar-, or hydro-power, to the final application, i.e., a vehicle driving a certain number of miles. The investigated fuels are hydrogen, methane, methanol, dimethyl ether and Diesel. While their production process is analyzed based on literature, the usage of these fuels is analyzed based on chassis dynanometer measurement data of various EURO-6b passenger vehicles. Conventional and hybrid power-trains as well as various carbon dioxide sources are investigated in two scenarios. The first reference scenario considers market-ready technology only, while the second future scenario considers technology which is currently being developed in industry and assumed to be market-ready in near future. With the results derived in this study and with consideration of boundary conditions, i.e., availability of infrastructure, storage technology of gaseous fuels, energy density requirements, etc., the most energy efficient of the corresponding suitable synthetic fuels can be chosen.